Germplasm screening of pearl millet (Pennisetum glaucum) for popping characteristics - CHAUHAN, S S; JHA, S K; JHA, G K; SHARMA, D K; SATYAVATHI, T; KUMARI, JYOTI (The Indian Journal of Agricultural Sciences, 2015)
Thirty eight germplasms/varieties of pearl millet (Pennisetum glaucum L. R Br) were screened for popping characteristics at optimum processing conditions. For determining optimum processing condition, popping experiment of pearl millet (PC 443) was initially carried out as per central composite rotatable design in response to surface methodology with three factors (moisture content, tempering time and popping temperature) at five levels. Optimum conditions for maximum popping yield (62%) was determined as 15.92% moisture content, 7.16 h tempering time, and 282°C temperature. The popped grains were found to have good nutritional value with 11.2% protein, 7.36% fat, 2.96% crude fibre, 3.83% ash, 72.81% carbohydrate, and total antioxidant 15.47 μ mole Trolox /100 g. Popping significantly reduced anti-nutritional factor to a level of 373.82 mg/100g phytic acid. Based on popping characteristics like popping yield, puffing index and size of popped grain, seven germplasms/varieties, viz. IC 283734, IC 283745, IC 283763, IC 283842, IC 283908, 841-B and PPMI 301 were found to have potential popping trait.